In vitro effect of marigold seed exudates on plant parasitic nematodes - Riga, Ekaterini; Hooper, Catharine; Potter, John (Phytoprotection, 2005)
Water extracts from seed exudates of Tagetes erecta cv. Crackerjack and T. patula var. polynema caused significantly higher mortality (P < 0.05) to Heterodera schachtii, Meloidogyne hapla and Pratylenchus penetrans than the control extracts from radish, tomato and corn seeds, respectively. Marigold seed exudates consist of nematicidal compounds. Nematostatic compounds have not been found in the seed exudates. Two high-performance liquid chromatography fractions derived from T. erecta cv. Crackerjack and one from T. patula var. polynema caused the highest mortality of H. schachtii in comparison with a water control and the rest of the fractions.